Determination of the melting layer from meteorological radar data - Abu Baker Sharif, Omer Abdel Razag Sharif (2006)
The bright band is the enhanced radar echo (reflectivity) associated with the melting of hydrometeors in stratiform rain. However, incorrect determination of the bright-band may lead to significant overestimation of precipitation such as rainfall rate reaching the ground, sometimes by as much as a factor of five, as in the example for rainfall rate. Radar has the potential to distinguish between different hydrometeors through the vertical profile of reflectivity by its statistical moments. The vertical profile can be used to determine the bright band. The main objective of this project is to determine the boundaries of the melting layer (bright band) based on the meteorological radar measurements. This determination includes the evaluation of the rain height and zero degree isotherms height. To achieve this description fully, the raw radar measurements have been sorted out, filtered, and decoded, plotted and analyzed. Radar observables have been plotted against the corresponding heights, and their boundaries have been determined according to the enhancement and transition of radar parameters. The results give an acceptable correlation with the international telecommunication union- radio communication sector (ITU-R) recommendations and a good one with the results that are obtained from the precipitation radar on-board the tropical rainfall measuring mission (TRMM) satellite and the characteristics of the melting layer in Singapore, which obtained using S-band polarization-diversity Doppler radar